Research on affective cognitive education and teacher–student relationship based on deep neural network - Zhou, Shi (Frontiers in Psychology, 2022)
Since entering the new century, People's living standards are constantly improving, with the continuous improvement of living conditions, people are becoming more and more important in education, which is the embodiment of the enhancement of national strength. The education level is getting higher and higher, and a good education level needs a good teacher-student relationship. To solve these problems, we use the emotional cognition of God's network to study the teacher-student relationship, and collect and analyze the data of the teacher-student relationship. In this chapter we use GABP neural network algorithm DHNN algorithm and discrete Hopfield neural network to make the collected data more convenient to be analyzed. The research shows that there is a close relationship between the educational level and the relationship between teachers and students in China, and a good relationship between teachers and students will promote the improvement of educational level. According to the research data"face-to-face" is the most important way of interaction between tutors and postgraduates in various types of teacher-student relationship. QQ WeChat is also one of the main ways of interaction between students and teachers, which shows that the interaction between students and teachers is talking about the interaction between online and Internet. The education industry is becoming more and more important, and the teacher-student relationship is the most important part of the education industry. Good teacher-student relationship is helpful to cultivate students' healthy personality. In view of the cold relationship between teachers and students at present, we need to make some measures the relationship between teachers and students, and effectively use the relationship between teachers and students to promote the better development of the education industry.